Autologous Iliac Bone Graft Compared with Biphasic Hydroxyapatite and Calcium Sulfate Cement for the Treatment of Bone Defects in Tibial Plateau Fractures: A Prospective, Randomized, Open-Label, Multicenter Study. (5th February 2020) - Hofmann, Alexander; Gorbulev, Stanislav; Guehring, Thorsten; Schulz, Arndt Peter; Schupfner, Rupert; Raschke, Michael; Huber-Wagner, Stefan; Rommens, Pol Maria; Al Sadi, Onays; Andruszkow, Hagen; Arand, Charlotte; Biberthaler, Peter; et al.
Abstract : Background: Bone-graft substitutes are commonly used for the augmentation of traumatic bone defects in tibial plateau fractures. However, their clinical performance compared with that of autologous bone-grafting, the gold standard in bone defect reconstruction, still remains under debate. This study investigates the differences in quality of life, pain, and radiographic outcomes in the treatment of tibial plateau fracture-associated bone defects with either autologous bone grafts or a bioresorbable hydroxyapatite and calcium sulfate cement (CERAMENT BONE VOID FILLER [CBVF]; BONESUPPORT). Methods: In this study, 135 patients with acute depression and split-depression fractures of the proximal part of the tibia (OTA/AO types 41-B2 and 41-B3) were enrolled in a prospective, controlled, randomized, multicenter trial including 20 hospitals in Germany. Patients were randomized to receive either autologous iliac bone graft or CBVF for reconstruction of the bone defect. The primary outcome measures were the Short Form (SF)-12 version 2 Physical Component Summary (PCS) score at week 26 (the study was designed to show noninferiority of the CBVF with regard to the PCS with a prespecified margin of −5 points) and the pain level at 26 weeks postoperatively measured by a visual analog scale (VAS). The secondary outcomes were the SF-12 version 2 Mental Component Summary (MCS) and SF-12 PCS scores at weeks 1, 6, and 12 and bone-healing on radiographs. Results: Age, sex, fixation methods, and fracture pattern were comparable in both groups. There were no significant differences (p > 0.05) in the SF-12 PCS or VAS scores at postoperative week 26. There was a significant reduction of blood loss (p = 0.007) and pain levels (p = 0.008) at postoperative day 1 in the CBVF group. The rates of fracture-healing, defect remodeling, and articular subsidence were not significantly different (p > 0.05) in both groups. Conclusions: Bioresorbable CBVF was noninferior to autologous bone graft with regard to both patient-reported and radiographic outcomes in tibial plateau fractures of OTA/AO types 41-B2 and 41-B3. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.